PENGARUH DISCOUNT & PERSONAL SELLING (SALES PROMOTION GIRL) TERHADAP KEPUTUSAN PEMBELIAN BRAND EMINA DI GUARDIAN BANDUNG - Geovani Nathania Nesya Novia Setiawan; Syahputra (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Beauty is a fast-growing industry. One of the beauty brands is Emina. Emina are sold in various offline stores such as Guardian, Guardian is spread across various cities in Indonesia including Bandung. This study looks at how the number of beauty brands sold at Guardian creates competition by relying on attractive discounts and personal selling through Sales Promotion Girl (SPG) to influence consumer purchasing decisions.This research applies a quantitative approach with a descriptive type of research, where sampling is done through a non-probability sampling method, with 208 valid respondents. The analysis techniques used include descriptive approaches and multiple linear regression analysis. Based on the results of descriptive analysis, the variables Discount, Personal Selling, and Purchase Decision show a very good percentage in their categories.The results showed that the Discount and Personal Selling variables together had a significant effect on the purchasing decision variable. Partially, the variables Discount and Personal selling each have an effect on purchasing decisions. The Coefficient of Determination produces 63.7%, which means that Discount and Personal Selling have a big influence on Purchasing Decisions.